Coporate Sosial Responsibility ''CSR Beyond Borders'' Colours Of Life at Arked Niaga Padang Besar Perlis - Jamali; Desti Umita Sari Sikumbang (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
The international community service program